"Fake news" and Christian freedom : the necessity for A dialogue - Simon, Benjamin (Array, 2018)
Politics and media development in our days is terrifying. Manipulation is dominating the social space. The so-called Overton window concept show us how, by way of "fake news" in a particular setting, certain completely unacceptable opinions slowly become part of the social consensus. Without understanding this change, people become deprived of their freedom and begin to feel more and more helpless. Five hundred years ago, theologian Martin Luther (1483-1546) rose against such attempts, defending his theological beliefs form estranged and twisted interpretations. In his essay, On Christian Freedom (1520), he took a firm position. Using a twofold thesis - that the Christian is both a free man and master of everything so he is not subjected to anyone, and that the Christian is also a humble servant to everyone and that he is subjected to everyone - he clarified that faith and love lead the Christian in all his activities and works. Luther clarified that in faith and love a fullness of the relationship between God and His loved ones - the mankind - is achieved, thus being humble does not mean giving up on our freedom; instead, it means to have the strength and courage to achieve it! Based on the four dimensions of freedom - political, social, identity, and dialogue - Luther provides an insight into his own understanding of freedom, which is still applicable in today’s social climate and the challenges of this age. These four dimensions helps the believer to take a clear stance against targeted attempts at deception which are immersed in "fake news."